A vállalati raktár logisztikai rendszer felépítése, anyaggazdálkodási jellemzők az ÉNYKK Zrt. esetében - Király Dominika (2019)
In my final thesis, I present the Északnyugat-magyaroszági Közlekedési Központ Zrt. warehouse logistics system structure, and materials management features, example on country Zala warehouses. I spent my internship Központi Raktár in Zalaegerszeg, so this is get great attention in my final thesis. Under my internship get lot of new information the material management features, and logistics processes. My final thesis purpose, that I present the company, which in 2015 was formed six wheel company. My main task, introduce the logistics processes, material management features, increase of stock in trade, and solution. First, I review the company, organization structure, order of operation, and services. I present the company logistics using the example Zalaegerszegi Központi Raktár. I introduce the organization structure, procurement process, warehouse logistics process, warehouses, facilities, material handling machines/ equipment, storage method, and consigment stock. I show the using ERP system, the SAP, and the logistics modul. In fine, I find the answers, and explanation of the increase of stock in trade. I analyse the stock in trade, and give some solution, for example vehicle fleet standardisation.